Stress and resistivity controls on in situ boron doped LPCVD polysilicon films for high-Q MEMS applications - 解婧 刘云飞 杨晋玲 唐龙娟 杨富华 (Journal of semiconductors, 2009)
The simultaneous control of residual stress and resistivity of polysilicon thin films by adjusting the deposition parameters and annealing conditions is studied. In situ boron doped polysilicon thin films deposited at 520 ℃ by low pressure chemical vapor deposition （LPCVD） are amorphous with relatively large compressive residual stress and high resistivity. Annealing the amorphous films in a temperature range of 600-800 ℃ gives polysilicon films nearly zero-stress and relatively low resistivity. The low residual stress and low resistivity make the polysilicon films attractive for potential applications in micro-electro-mechanical-systems （MEMS） devices, especially in high resonance frequency （high-f） and high quality factor （high-Q） MEMS resonators. In addition, polysilicon thin films deposited at 570 ℃ and those without the post annealing process have low resistivities of 2-5 mΩ·cm. These reported approaches avoid the high temperature annealing process （〉 1000 ℃）, and the promising properties of these films make them suitable for high-Q and high-f MEMS devices.